Carve The Mark - Roth, Veronica; Butler, Austin 1991-; Rankin, Emily ([New York, New York] : Harper Audio, 2017)
On a planet where violence and vengeance rule, in a galaxy where some are favored by fate, everyone develops a Currentgift, a unique power meant to shape the future. While most benefit from their Currentgifts, Akos and Cyra do not. Their gifts make them vulnerable to others' control. Can they reclaim their gifts, their fates, and their lives, and reset the balance of power in this world?
Keywords: Ability -- Juvenile fiction; Survival -- Juvenile fiction; Ability -- Fiction; Survival -- Fiction; Science fiction; Children's audiobooks